The Different Inhibition of Return (IOR) Effects of Emergency Managerial Experts and Novices: An Event-Related Potentials Study - Cao, Rong; Wu, Lü; Wang, Shuzhen (Frontiers in Behavioral Neuroscience, 2017)
Inhibition of return (IOR) is an important effect of attention. However, the IOR of emergency managerial expert is unknown. By employing real emergency and natural scene pictures in expert-novice paradigm, the present study explored the neural mechanism underlying the IOR effects of emergency managerial expert and novice. The interested data were IOR effects elicited by the post-cued emergency pictures both in behavioral and ERPs levels. In experiment1, behavioral results showed that the IOR was robust when SOA is 400ms. ERPs results showed a larger N1 and N2 and a smaller P3 at SOA of 200ms, relative to SOA of 400ms. In experiment2, behavioral results showed that the IOR was robust at SOA of 200ms. ERPs results showed that an enhanced N2 at SOA of 200ms; the enhanced N2 and attenuated P3 at cued location in the right parietal lobe and adjacent brain regions than uncued location at SOA of 200ms. The findings of the two experiments showed that, relative to the novice, IOR for the emergency managerial expert was robust earlier, and dominated in the right parietal lobe and adjacent brain regions, suggesting more flexible attentional processing and higher visual search efficiency of the emergency managerial expert. The findings of the present study indicate that the P3, possible N2, over the right parietal lobe and adjacent brain regions are the biological indicators for IOR elicited by post-cued emergency pictures for emergency managerial expert.